Gender Equity and Transformational Leadership Style in Corporate World - Ojo, Funmilayo Yemi; Adeosun, Foluke O. (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Organizations are realizing that, in order to adequately address human resources concerns, they must develop long-term as well as short term solutions to gender and leadership issues. When it comes to gender and leadership, one thing is clear, women can be successful in leading both private and public sector organizations. With the advent of the new millennium, the range and numbers of women in top positions across fields of endeavour have increased dramatically. Organizations are very interested in assessing leadership competencies for both performance appraisal and leadership development purposes. However, when examining the cases of top women leaders, similar stories do not seem to emerge. This paper specifically considers literature on gender equity and transformational leadership style in the corporate world.